2017
DOI: 10.1175/jhm-d-17-0021.1
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Probabilistic Downscaling Methods to Develop Streamflow Forecasts from Climate Forecasts

Abstract: Statistical information from ensembles of climate forecasts can be utilized in improving the streamflow predictions by using different downscaling methods. This study investigates the use of multinomial logistic regression (MLR) in downscaling large-scale ensemble climate forecasts into basin-scale probabilistic streamflow forecasts of categorical events over major river basins across the U.S. Sun Belt. The performance of MLR is then compared with the categorical forecasts estimated from the traditional approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…These limitations can inhibit future planning and management (Stagnitta et al 2018). Therefore, mathematical modeling is often employed as an alternative to the direct measurement of river flows (Mazrooei and Sankarasubramanian 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These limitations can inhibit future planning and management (Stagnitta et al 2018). Therefore, mathematical modeling is often employed as an alternative to the direct measurement of river flows (Mazrooei and Sankarasubramanian 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Integration of the ECHAM4.5 precipitation forecasts with the NLDAS-2 non-precipitation forcing variables supports the idea of evaluating the LSM in realtime SM forecasting. Our previous studies have also showed the robust performance of ECHAM4.5 forecasts for improving streamflow forecasting (Sinha et al, 2014;Mazrooei and Sankarasubramanian, 2017). Both forecast verification metrics, correlation coefficient and RMSE, show that the forecasted SM captures the variability in SMAP observations with decent accuracy.…”
Section: Discussionmentioning
confidence: 79%
“…Integration of the ECHAM4.5 precipitation forecasts with the NLDAS-2 non-precipitation forcing variables supports the idea to evaluate the LSM in real-time SM forecasting. Our previous studies have also showed the robust performance of ECHAM4.5 forecasts for improving streamflow forecasting (Sinha et al, 2014;Mazrooei and Sankarasubramanian, 2017). Both forecast verification metrics, correlation coefficient and RMSE, show that the forecasted SM captures the variability in SMAP observations with decent accuracy.…”
Section: Discussionmentioning
confidence: 79%